Ferroelectric stability of annealed PVDF-TrFE thin film incorporated with MgO nanofillers - Wahid, Mohamad Hafiz Mohd; Dahan, Rozana Mohd; Arshad, Adillah Nurashikin; Zulkefle, Habibah; Sa'ad, Siti Zaleha; Mahmood, Mohamad Rusop; Gan, Wee Chen; Abd Majid, Wan Haliza (Universiti Putra Malaysia, 2017)
Spin coated polyvinlylidenefluoride-trifluoroetylene (PVDF-TrFE 70/30mol%) copolymer thin film were initially produced and annealed at varying temperatures (100°C to 160°C). The morphology, dielectric and ferroelectric analysis showed that PVDF-TrFE film annealed at 120°C produced the highest remnant polarization, Pr of 92 mC/m2, with orderly and grain-like shaped crystallites. The filled PVDF-TrFE, loaded with various volume percentages (1 – 7%) of Magnesium Oxide (MgO) nanofillers and then, annealed at 120°C, produced homogenous filler distribution with low agglomerates, especially for 3% PVDF-TrFE filled films. Moreover, the annealed PVDF-TrFE/MgO(3%) generated the highest value of Pr in comparison to the other filled nanocomposite thin films. Most importantly, the saturation of hysteresis loop, Ps for annealed PVDF-TrFE/MgO(3%) film was relatively improved by 20% as compared to the unfilled annealed thin film. This study established that, 3% MgO loaded in PVDF-TrFE thin film and annealed at 120 °C demonstrated a stable ferroelectric thin film, closed to an ideal ferroelectric film, in which the ratio Pr/Ps for the film established a value approaching unity (value of 1).